O povoado pré-histórico do Outeiro Redondo (Sesimbra): resultados das campanhas de escavação de 2013 e 2014 - Cardoso, João Luís (2017)
We present the results of the archaeological excavations at the fortified Chalcolithic settlement of Outeiro Redondo, Sesimbra in 2013 and 2014. These two campaigns continued the excavations performed there between 2005 and 2008. The defensive and housing structures were identified. The defensive structures corresponds to two constructive phases belonging to the Full / Late Chalcolithic. The housing structures corresponds also to two constructive phases, one of the Early Chalcolithic, the other of the Full / Late Chalcolithic. Thus, we may conclude that the first moment of this chalcolithic site corresponds to an open, unfortified settlement. An abundant and diversified set of artifacts were recovered during the excavations, pointing out to this settlement’s economic activities and the intensity of the human successive occupations of the place. Copper metallurgy stands out as a main economic activity in this site. A large entrance devoid of functional characteristics facing the sea, suggests the existence of ritual practices. In fact, the importance of the sea is confirmed by a foundational ritual, with the concealment, in a small cavity excavated in the substrate, of a mussel shell of exceptional dimensions. This shell seems to emphasize the importance of marine resources in the economy and daily life of the first community installed there, during the transition from the first to the second half of the 3rd millennium BC.